An improved TDCP-GNSS/INS integration scheme considering small cycle slip for low-cost land vehicular applications. (24th March 2021) - Chen, Kai; Chang, Guobin; Chen, Chao; Zhu, Ting
Abstract: An improved global navigation satellite system (GNSS)/inertial navigation system (INS) tightly coupled scheme based on a time-differenced carrier phase (TDCP) was proposed for a low-cost vehicle navigation system. The proposed scheme aims to improve the navigation performance and computational efficiency of the system for low-cost GNSS receivers and low-accuracy INS. The traditional measurement model based on the TDCP has either high accuracy with a large computational load or high efficiency with low accuracy. Considering both the positioning accuracy and computational burden, an accurate and efficient measurement model was derived in this paper. In positioning based on the carrier phase, it is an indispensable task to handle the cycle slips, especially small ones. However, the cycle slip of a certain moment only contaminates the current TDCP measurement, but not the subsequent TDCP measurements. Based on this characteristic of the TDCP measurement, a novel cycle slip processing strategy was proposed for the TDCP-GNSS/INS integration scheme, in which cycle slip is directly handled as a gross error with a robust extended Kalman filter (EKF). The vehicular test has been conducted to evaluate the performance of the improved TDCP-GNSS/INS integration scheme. Experiment results show: (a) compared with the traditional position error parameter-based measurement model, the proposed measurement model can improve the accuracy of the horizontal and vertical position by 58.4% and 12.5%, respectively. Compared with the traditional velocity error parameter-based measurement model, the proposed measurement model does not improve the positioning accuracy, but improves the computational efficiency by 25.2%. (b) The strategy of treating cycle slip as a gross error is feasible in the TDCP-GNSS/INS tightly coupled navigation system. Although a small cycle slip can seriously affect the positioning performance of the system, the robust EKF can effectively avoid the long-term harm caused by small cycle slips.